2022
DOI: 10.1002/jsfa.12370
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and molecular docking analyses of novel calcium‐chelating peptide from soy yogurt and the study of its calcium chelation mechanism

Abstract: BACKGROUND Calcium is an essential dietary mineral nutrient for humans. Digestive instability limits the bioavailability of calcium ions. Peptide–calcium chelate has been proven to excite higher calcium absorption than amino acid–calcium chelate, organic and inorganic calcium. Soy yogurt, which is produced via liquid‐state fermentation using lactic acid bacteria, has a high amount of bioavailable calcium. In this study, a novel peptide with high calcium binding affinity was purified and identified from soy yog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In our preliminary experiments, DEDEQIPSHPPR dodecapeptide from soy yogurt was confirmed to possess 36.64 ± 0.04 mg/g calcium-chelating capacity (14). Previous studies found that the calcium chelation capacity is closely related to their molecular mass, amino acid compositions, sequences, and spatial conformation (15,16).…”
Section: Introductionmentioning
confidence: 55%
“…In our preliminary experiments, DEDEQIPSHPPR dodecapeptide from soy yogurt was confirmed to possess 36.64 ± 0.04 mg/g calcium-chelating capacity (14). Previous studies found that the calcium chelation capacity is closely related to their molecular mass, amino acid compositions, sequences, and spatial conformation (15,16).…”
Section: Introductionmentioning
confidence: 55%
“…It has been shown that the molecular weight distribution of peptides is critical for calcium–peptide binding, with fragments with molecular weights below 3000 Da having higher calcium binding capacity. 29 However, more small molecules (<500 Da) in the wheat germ hydrolysis products were detrimental to the calcium-binding capacity. 30 Secondly, on the peptide sequences of the DSPs, a plurality of peptides, such as VPGPMGPSGPR, GDAGPAGPK, GPAGPAGGPR, GPVGPAG, and so on, have triplet repeats of the (Gly-X-Y)n primary structure of the collagen peptide chain.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, pH in the gastric phase is very low, and the hydrolysis of proteins is inefficient. Therefore, in addition to this theory, some types of MCPs or hydrolysates with low molecular weights or synthetic MCPs can remain intact during the whole digestion because these peptides are not sensitive to both pepsin and pancreatic enzymes (Gan, Xiao, et al., 2022). For instance, the molecular weight of a synthetic sea cucumber peptide–zinc complex remained almost unchanged after GI digestion, implying that synthetic MCPs remain stable in GI digestion environments (Wang, Sun, et al., 2022).…”
Section: Digestions and Absorptions Of Mcp–metal Complexesmentioning
confidence: 99%